DEPRESI INDUCED STEROID: STUDI KASUS - Saiful Batubara (Jurnal Penelitian Farmasi & Herbal, 2019)
Back Ground: Depression is a natural disturbance of feeling that is characterized by feelings of sadness, loss of interest and easily tired. Steroids are drugs that can reduce swelling, pain and heat due to inflammation through reducing the immune response. Steroids are often used in cases of systemic Lupus Erythematosus in the long term. Therefore management of the disease must be done well because steroids can cause depression. Case Report:Women, 37 years old, depressed mood, disappointment in life, loss of enthusiasm, fatigue, decreased appetite and difficulty sleeping for 1 year. 4 years ago I took steroids for 2 years at a dose of 20mg / day, because rheumatoid arthritis was stopped by os, and for the past 1 year, steroid consumption was due to Systemic Lupus Erythematosus around 60 mg / day. . Before the os consumes steroids, the OS has never experienced depression.BP: 110/70 mmHg , HR 88x/menit, RR 20x/menit, Temp 37°C. Skor BDI 21. Laboratorium Hb 11,8 g/dl, Leukosit 7500/mm3, trombosit 201.000/mm3,,Kalium 2,8, KGDad 99 mg/dlSGOT 29 ,SGPT32, Ureum 15,78 mg/dl, Creatinin 0,65 mg/dl. Tot Colesterol 198mg/dl, LDL 128 mg/dl, HDL 35 mg/dl Fototoraks : Jantung dan Parudalambatas normal, FotoLumbosakral : SpondilosisLumbalis. The patient is diagnosed with depression. Given psychotherapy, sandepril 2 x 25 mg for 3 months. Patients show clinical improvement marked by reduced sadness and can understand the disease. Conclusion :Steroid-induced depression has been reported after psychotherapy and sandepril 2 x 25 mg of the patient's condition showed improvement.